Adesão de pacientes hipertensos ao tratamento medicamentoso - Bezerra, Amanda Silva de Macêdo (2014)
This is a descriptive, cross-sectional study, conducted in a center of Hypertension and Metabolism, which aimed to identify adherence to drug therapy in hypertensive patients, and to identify the factors, directly related to the patient, associated with this adherence. The sample consisted of 77 patients and the instrument used to verify patient compliance was the Measure of Adherence to Treatment and a semi-structured questionnaire consisting of factors for non-adherence to drug treatment. The results showed adherence of 87% of hypertensive patients. Factors directly related to the patient, which were associated with the adherence, were: the place of origin; patients' self-assessment of blood pressure levels; willingness to abandon treatment and patient acceptance of the disease.